Teaching Muslim Representation in Film Using Bell Hooks' Theoretical Intervention: Collapsing the Real and Imaginary - Mubarak, Hadia (Teaching theology and religion, 2025)
In Reel to Real: Race, Class, and Sex at the Movies, a collection of profound and paradigm-shifting essays on film, Bell Hooks (1996) writes, “Whether we like it or not, cinema assumes a pedagogical role in the lives of many. It may not be the intent of a filmmaker to teach audiences anything, but that does not mean that lessons are not learned” (pp. 2–3). Hooks' compelling argument forms the theoretical backdrop of my course, Muslims in Pop Culture, which examines the ways in which the genre of film constructs an image of Muslims as an imaginary “Other” in the American public consciousness. Through multiple case studies, students explore how films often affirm pre-existing biases about Muslims embedded in the frameworks of Orientalism, Gendered Orientalism and the “Clash of Civilizations” theory. The course cultivates students' critical consciousness of films' pedagogical power to mediate viewers' understanding of the real Muslim world.